The Gender-Career Estimation Gap - Lutz C. Kaiser (Institute for the Study of Labor (IZA), 2014)
The paper discusses gender differences with regard to the self- and reciprocal estimation of career expectations. Firstly, the theoretical background and the literature are identified. Within this frame, the instance of self-under-estimated career prospects of female workers and statistical discrimination in the labor market are described. Both aspects are jointly assessed as a self-fulfilling prophecy-phenomenon redounded to women's disadvantage on the labor market. Secondly, the empirical part analysis the respective self- and reciprocal estimation of female and male career prospects for public sector workers in Germany. The results display obvious discrepancies between self- and reciprocally estimated career expectations that constitute a gender-career estimation gap. As the German public sector contains specific devices to equalising career chances of male and female employees, the findings even underpin the insistency of under-estimated career prospects of female workers despite the existing public sector regime of equality. Finally, approaches of how to equalize male and female career chances are critically reviewed.
Keywords: J16; J24; J4; J71; J78; 330; self- and reciprocal estimation of career opportunities; self-fulfilling prophecy; gender-career estimation gap; statistical discrimination; public sector